OPINI MAHASISWA ILMU KOMUNIKASI UMS TENTANG BERITA HOAX POLITIK DI MEDIA SOSIAL TWITTER - Bedjo Sukarno, Siswanta, Maharani Wulan Agustin, (Solidaritas, 2018)
AbstractTwitter is able to form a diverse public opinion through the dissemination of information widely and quickly. The background of this issue is twitter as an application that many young people including students still love it until now. Twitter is a photo sharing application, status updates with digital images, and share it using hashtags. Twitters common usage as a place to upload photos and share opinions to other users. Twitter spreading a lot of political hoax news that ca harm and even divide many parties. Political hoax news is a false preaching or deceitful attempt, outsmarting the reader or listener to believe in something, whereas the false creator of the news knows that the news is false. This research described how the political hoax news through social media of twitter affects the opinion of students of the Faculty of Communication of the Universitas Muhammadiyah Surakarta.Located at the Universitas Muhammadiyah Surakarta. This research used the theories from William Albiq said that a number of opinions from the opinions of individuals who obtained through debate and public opinion is the result of interaction between individuals in a public. Technique of collecting data obtained by purposive sampling through interview with information, observation and documentation. The results obtained show that the political hoax news circulating in social media of twitter did not give influenced that could harm or enmity among the students. Students are looking for a reliable source of news. With the news of political hoax circulating nitizens was troubled, but no matter and no favors.Keywords: Twitter, News Hoax, Public Opinion